The Role of the Chamber of Commerce and Industry in Padang in the Colonial Economic Structure, 1907-1940. - Benny Hamdani (CV. Fahr Publishing, 2023)
This article analyzes the role of the Kamer van Koophandel en Nijverheid te Padang (Chamber of Commerce and Industry of Padang) in the colonial economic structure, a aspect that has been overlooked in Indonesian economic historiography. The research aims to construct a narrative about the Kamer van Koophandel en Nijverheid te Padang and its role within the colonial economic framework. Through historical methods, the study finds that the establishment of the Kamer van Koophandel en Nijverheid te Padang is closely tied to the European countries' threats to colonial territories. Java served as the central power base for the Dutch, while areas outside Java were marginalized. In order to prevent these marginalized regions from falling into the hands of other European nations, the Dutch sought to integrate the non-Javanese regions with Java, achieved in part through the opening of trade routes in Padang and Makassar in 1852. Padang emerged as the most prominent area outside Java (Buitenbezittingen). Several years after the opening of these routes, the Kamer van Koophandel en Nijverheid te Padang was established through a decree by the Dutch East Indies government. This institution provided a platform for Indo-European entrepreneurs, particularly those of Dutch origin in Padang, to anticipate the growth of trade and shipping on the western coast. The presence of the Kamer van Koophandel en Nijverheid te Padang played a significant role in the colonial economy of Padang. It engaged in various sectors, including import-export, shipping, expeditions, banking credit, mining, agriculture, industry, and more. In the pursuit of business endeavors, economic lobbying was often employed. Keywords: Chamber of Commerce and Industry, KADIN, export, import, lobbying, economic history